The relevance of Ibn Khaldun’s agricultural economic thoughts during the Covid-19 pandemic - Anwar, Khairul; Jailani, Novalini; Damayanti, Dhea Aulia (Journal of Islamic Economics Management and Business (JIEMB), 2022)
As an agricultural country, the agricultural sector in Indonesia has an important role in national economic development. Among Muslim thinkers, Ibn Khaldun is a figure who pays attention to agriculture and sees it as a vital source of life. This study aims to identify and analyze Ibn Khaldun’s concept of agricultural economics and its relevance during the Covid-19 pandemic, which has impacted the economic sector. This research is a type of library research using qualitative methods. While the data analysis technique used is descriptive qualitative. The primary data of this research are books, journals, essays, and news about the core issue, namely Ibn Khaldun’s view on agriculture which is then related to conditions in the era of the Covid-19 outbreak. The results show that Ibn Khaldun’s thoughts on the agricultural economy and the state’s role in serving the community are still very relevant during the Covid-19 pandemic. Agriculture, according to Ibn Khaldun, is the source of life. During the Covid-19 pandemic, the agricultural sector has been unaffected. This research is done to learn material for the community, especially about Ibn Khaldun’s thoughts in general, economics and agriculture in particular.